Combination of cytogenetic classification and MRD status correlates with outcome of autologous versus allogeneic stem cell transplantation in adults with primary acute myeloid leukemia in first remission. (April 2017) - Yao, Jianfeng; Zhang, Guixin; Liang, Chen; Li, Gang; Chen, Xin; Ma, Qiaoling; Zhai, Weihua; Yang, Donglin; He, Yi; Jiang, Erlie; Feng, Sizhou; Han, Mingzhe
Highlights: Both cytogenetic classification and MRD could independently predict the prognosis. Auto- & allo-SCT offer similar DFS for MRD neg AML with low and intermediate risk. Combination of cytogenetic risk and MRD status helps choosing auto- or allo-SCT. Abstract: Both autologous and allogeneic stem cell transplantation (auto- and allo-SCT) are treatment choice for adults with acute myeloid leukemia (AML) after complete remission (CR). However, the decision-making remains controversial in some situations. To figure out the treatment choice, we retrospectively investigated 172 consecutive patients with primary AML who received auto- ( n  = 46) or allo-SCT ( n  = 126) from a single transplant center. Auto- and allo-SCT group demonstrated comparable overall survival (OS) and disease-free survival (DFS) ( P  = 0.616, P  = 0.559, respectively). Cytogenetic classification and minimal residual disease (MRD) after one course of consolidation were identified as independent risk factors for DFS (hazard ratio (HR), 1.800; 95% CI, 1.172–2.763; P  = 0.007; HR, 2.042; 95%CI, 1.003–4.154; P  = 0.049; respectively). We subsequently found that auto- and allo-SCT offered comparable DFS to patients with favorable or intermediate risk and were tested MRD neg after one course of consolidation ( P  = 0.270) otherwise auto-SCT were inferior due to increased risk of leukemia relapse. Our study indicated that the combination of cytogenetic classification and MRD monitoring correlated with outcome of auto- versus allo-SCT and might help the choice between the two types of SCT for adults with primary AML, which is of significance for patients with expected intermediate prognosis in the current scenario.